2009
DOI: 10.1108/13664380910977619
|View full text |Cite
|
Sign up to set email alerts
|

The impact of contractors' management capability on cost and time performance of construction projects in Nigeria

Abstract: Purpose -Management capability is one of the major criteria for evaluating construction contractors during prequalification and tender evaluation This paper aims to investigate the impact of contractors' management capability as a prequalification criterion on cost and time performance of selected building projects. Design/methodology/approach -Prequalification assessments of management capability of wining contractors as well as cost data relating to 77 completed building projects executed between 2004 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 22 publications
2
35
0
3
Order By: Relevance
“…Thus indicated that time performance of civil engineering project was independent of contractors' management ability. Hence, this study believed that relying on contractors' managerial capability in respect of civil engineering project could lead to failure as far as time performance is concerned contrary to the opinions expressed in [41,42].…”
Section: Impact Of Contractors' Prequalification Criteria On Time Permentioning
confidence: 69%
See 3 more Smart Citations
“…Thus indicated that time performance of civil engineering project was independent of contractors' management ability. Hence, this study believed that relying on contractors' managerial capability in respect of civil engineering project could lead to failure as far as time performance is concerned contrary to the opinions expressed in [41,42].…”
Section: Impact Of Contractors' Prequalification Criteria On Time Permentioning
confidence: 69%
“…This implied that a strong relationship existed between time performance of civil engineering project and contractors' reputation. Besides, the outcome of this research quite negated the result in [41]. Despite [41] placing construction projects on same platform, management capability emerged the criterion that impact most on time performance.…”
Section: Impact Of Contractors' Prequalification Criteria On Time Permentioning
confidence: 78%
See 2 more Smart Citations
“…Statybų sektorius -vienas svarbiausių gamybos sektorių tiek Lietuvoje, tiek visoje Europos Sąjungoje (ES). Tai pagrindinis sektorius, kuris skatina augti ekonomiką besivystančiose šalyse (Aje et al 2009), didina vidaus paklausą ir užimtumą kituose sektoriuose (Ye at al. 2009), juo remiantis kuriamos tiesioginės ir netiesioginės darbo vietos, o į biudžetą surenkami mokesčiai.…”
Section: Statybos Projektas Bei Jo Valdymas: Samprata Ir Apibrėžimasunclassified